Causal relationship between asthma and hernia risk - Yao Lu; Huiping Yuan; Debing Li; Guanghui Yang; Xu Liu; Xian Wang; Ke Zhang; Dechun Liu (Medicine, 2026)
Epidemiological associations between asthma and various hernia subtypes have been reported, but the causality and direction remain unclear. This study employs a two‑sample Mendelian randomization (MR) approach to systematically assess the causal associations between asthma and 6 hernia subtypes. Using publicly available summary data of genome-wide association studies, asthma was selected as the exposure, and diaphragmatic hernia, umbilical hernia, femoral hernia, hiatus hernia, inguinal hernia, and ventral hernia were selected as outcomes. Instrumental variables were strictly screened ( F -statistic > 10). The inverse‑variance weighted method was used as the primary analytical approach, supplemented with MR Egger and weighted median methods. Sensitivity analyses included heterogeneity tests, horizontal pleiotropy tests, Steiger directionality tests, leave‑one‑out analyses, and Radial MR. Reverse MR was performed for validation. Forward MR analyses revealed a significant positive causal effect of asthma on diaphragmatic hernia (odds ratio [OR] = 1.19, 95% confidence interval [CI]: 1.08–1.31, P < .001) and a suggestive association with umbilical hernia (OR = 1.19, 95% CI: 1.05–1.34, P = .007). The umbilical hernia association was significant only by the inverse‑variance weighted method; weighted median ( P = .102) and MR-Egger ( P = .210) estimates were not statistically significant, and the estimate attenuated after outlier removal (confirmatory OR = 1.13, 95% CI: 1.01–1.26, P = .028). Sensitivity analyses showed no significant heterogeneity or pleiotropy. Reverse MR did not identify significant causal effects of hernias on asthma, although power limitations for certain hernia subtypes should be considered. No significant associations were observed between asthma and the other hernia subtypes, although the null findings for femoral and ventral hernias should be interpreted with caution due to limited statistical power. This study provides genetic evidence supporting asthma as a causal risk factor for diaphragmatic hernia, with a suggestive association for umbilical hernia. The diaphragmatic hernia finding was robust across multiple sensitivity analyses, whereas the umbilical hernia association was less consistent and requires further confirmation. These findings contribute to a deeper understanding of the mechanistic links between asthma and specific hernia subtypes.